Dzikir Manaqib Syekh Abdul Qodir Al-Jailani dalam Pemberdayaan Masyarakat di Ponpes. Al-Qodiri Jember: The Dhikr of Manaqib of Sheikh Abdul Qadir Al-Jailani in Community Empowerment at Al-Qodiri Islamic Boarding School, Jember - M. Walid (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2008)
In the modern era marked by spiritual crisis and psychological anxiety, Islamic mystical practices such as dhikr have emerged as a vital alternative for social rehabilitation. This study aims to analyze the empowerment of society through Dzikir Manaqib Syekh Abdul Qodir Al-Jailani at Al-Qodiri Islamic Boarding School, Jember, using a qualitative case study with a phenomenological approach. Data were collected through participant observation, in-depth interviews, and documentary techniques, then analyzed using grounded research and critical hermeneutics. The findings reveal that this dhikr practice empowers society in three multidimensional areas: worship, economy, and education. In worship, it fosters sincerity, repentance, and spiritual devotion. In the economy, it creates a marketplace for vendors and generates material blessings through collective prayer. In education, it instills values such as consistency, simplicity, ukhuwah Islamiah, and inner purification. The study concludes that Dzikir Manaqib serves as an effective instrument for community empowerment, offering a model of spirituality-based social development. Recommendations include integrating such practices into broader community development programs. Di era modern yang ditandai dengan krisis spiritual dan kecemasan psikologis, praktik keagamaan Islam seperti dzikir muncul sebagai alternatif penting bagi rehabilitasi sosial. Penelitian ini bertujuan menganalisis pemberdayaan masyarakat melalui Dzikir Manaqib Syekh Abdul Qodir Al-Jailani di Pondok Pesantren Al-Qodiri Jember, menggunakan pendekatan kualitatif studi kasus dengan metode fenomenologi. Data dikumpulkan melalui observasi partisipan, wawancara mendalam, dan teknik dokumenter, kemudian dianalisis dengan grounded research dan hermeneutika kritis. Temuan penelitian menunjukkan bahwa praktik dzikir ini memberdayakan masyarakat dalam tiga bidang multidimensi: ibadah, ekonomi, dan pendidikan. Dalam ibadah, dzikir menumbuhkan keikhlasan, taubat, dan ketakwaan. Dalam ekonomi, aktivitas ini menciptakan pasar pedagang dan mendatangkan berkah material melalui doa bersama. Dalam pendidikan, dzikir menanamkan nilai-nilai seperti istiqomah, kesederhanaan, ukhuwah Islamiah, dan pembersihan hati. Penelitian ini menyimpulkan bahwa Dzikir Manaqib merupakan instrumen efektif untuk pemberdayaan masyarakat berbasis spiritualitas. Rekomendasinya adalah mengintegrasikan praktik serupa ke dalam program pengembangan masyarakat yang lebih luas.